Cytokines and chemokines in follicular fluids and potential of the corresponding embryo: the role of granulocyte colony-stimulating factor - Nathalie Ledée; Raoul Lombroso; Letizia Lombardelli; J. Selva; Sylvie Dubanchet; G. Chaouat; Françis Frankenne; Jean Michel Foidart; Enrico Maggi; Sergio Romagnani; Y. Ville; Marie‐Pierre Piccinni (2008)
The cytokine/chemokine levels of individual follicular fluids (FFs) were measured to determine whether a biomarker could be linked to the developmental potential of the derived embryo.Fluid was collected from 132 individual FFs that were the source of oocytes subsequently fertilized and transferred. In each, a bead-based multiplex sandwich immunoassay (Luminex) was used to measure 28 cytokines and chemokines simultaneously.Significantly higher levels of interleukin (IL-2) and interferon (IFN-gamma) were detected in FF for embryos that underwent early cleavage. IL-12 was significantly higher in FF corresponding to highly fragmented embryos and the chemokine CCL5 was significantly higher in FF related to the best quality (Top) embryos. The level of granulocyte colony-stimulating factor (G-CSF) in individual FF samples was correlated with the implantation potential of the corresponding embryo. The area under the receiver operating characteristics curve, which distinguished the embryos that definitely led to delivery from those that did not, was 0.84 (0.75-0.90) (P = 0.0001) for FF G-CSF. FF G-CSF was significantly lower in patients older than 36 years compared with those <30-year old. When the FF G-CSF was 20 pg/ml or higher, the ratio between Top and non-Top embryos was significantly higher than for the group with FF G-CSF below 20 pg/ml (45 versus 20.45%, P = 0.007).Individual FF composition is related to the development of the corresponding in vitro generated embryo and its potential of implantation. Individual FF G-CSF may provide a non-invasive biomarker of implantation that needs to be evaluated together with in vitro observation to select the oocyte, and hence the embryo, to transfer.